2021
DOI: 10.1101/2021.01.13.426506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Layer 6A pyramidal cells subtypes form synaptic microcircuits with distinct functional and structural properties

Abstract: Neocortical layer 6 plays a crucial role in sensorimotor coordination and integration through functionally segregated circuits linking intracortical and subcortical areas. However, because of the high neuronal heterogeneity and sparse intralaminar connectivity data on the cell-type specific synaptic microcircuits in layer 6 remain few and far between. To address this issue, whole-cell recordings combined with morphological reconstructions have been used to identify morphoelectric types of layer 6A pyramidal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…Compared with other recent morphological studies, not using genetic targeting, the L6‐Ntsr1 cells are similar to the ‘L6A‐CT cell’ category in the study of Yang et al (2021). The L6‐Drd1a cells have similarities to the category ‘pyramidal L6B’ cells (Marx et al, 2015; Marx & Feldmeyer, 2013).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Compared with other recent morphological studies, not using genetic targeting, the L6‐Ntsr1 cells are similar to the ‘L6A‐CT cell’ category in the study of Yang et al (2021). The L6‐Drd1a cells have similarities to the category ‘pyramidal L6B’ cells (Marx et al, 2015; Marx & Feldmeyer, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…Results from both, in vitro and in vivo experiments indicate that L6‐Ntsr1 and L6‐Drd1a cells are involved in different CT circuits (Ansorge et al, 2020; Crandall et al, 2015; Kim et al, 2014; Lee et al, 2012; Olsen et al, 2012; Pauzin & Krieger, 2018), but less is known about differences in basic electrical properties, cell anatomy and how susceptible the development of the two cell types are to changes in sensory input during the early postnatal development. Previous studies comparing unlabelled CT and corticocortical pyramidal cells reported that corticocortical neurons were distinguished from CT cells based on anatomical and intrinsic membrane properties (Kumar & Ohana, 2008; Yang et al, 2021). Similar differences in anatomical and physiological properties have been described in other layers, for example, for layer 5 pyramidal cells (Groh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing activity affects both the probability of vesicle release and the quantal response amplitude, causing a combination of short-term facilitation and depression (transient strengthening or weakening of the synaptic "weight"). The dynamical properties of cortical synapses are influenced by both the presynaptic and postsynaptic cell types (15)(16)(17)(18)(19)(20) and endow neuronal networks with essential sources of computational diversity (21,22) . Synaptic physiology studies rarely include comprehensive descriptions of these dynamics, despite their functional importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing activity affects both the probability of vesicle release and the quantal response amplitude, causing a combination of short-term facilitation or depression (transient strengthening or weakening of the synaptic "weight"). The dynamical properties of synapses in the cortex are influenced by both the presynaptic and postsynaptic cell types (Reyes et al, 1998;Blackman et al, 2013;Larsen and Sjöström, 2015;Markram et al, 2015;Lefort and Petersen, 2017;Yang et al, 2021)and endow neuronal networks with essential sources of computational diversity (Abbott and Regehr, 2004;Llera-Montero et al, 2019). Using new analyses and models, we have characterized the stochasticity and short term plasticity of over 1000 synapses, offering a more comprehensive view of the diversity of cortical synapse types.…”
Section: Introductionmentioning
confidence: 99%